The Using of Visual Auditory Read Kinesthetic to Improve Students Reading Ability - Dinar Vincy Yunitaka Bahrudin (Universitas Madura, 2018)
Reading is a very important skill to be mastered by every students. Reading is a complex ability. The readers not only look at the symbols written alone, but trying to understand the meaning of the written symbols itself. A good teacher need some method to make students easy in understand the message or the content of a text. Visual Auditory Read Kinesthetic (VARK) model is a new alternative method that is modified by utilizing the modalities held by students. The possess of VARK including visual, hearing, and kinesthetic styles. By applying this model, at the end of the learning process, students are rewarded for their work where the teacher and the entire class applaud. Teachers can also say